Decomposition of [2-Pyr(SiMe3)(2)C](2)SbCl into the stibaalkene [2-Pyr(SiMe3)(2)C-Sb=C(SiMe3)2-Pyr]: Solid, solution, and a initio study - Andrews, P; McGrady, J; Nichols, P (2004)
The disubstituted antimony chloride complex [2-Pyr(SiMe3)2C]2SbCl (Pyr = C5H4N), formed from the 2:1 reaction of [2-Pyr(SiMe3)2CLi·tmeda] with SbCl3, readily decomposes into the stibaalkene species [2-Pyr(SiMe3)2CSb=C(SiMe3)2-Pyr] via β-elimination of Me3SiCl. The stibaalkene species is an intensely colored, highly air and moisture sensitive, deep red oil. In thf solution the elimination of Me3SiCl occurs at temperatures ca. -40°C; however, orange crystals of [2-Pyr(SiMe3)2C]2SbCl were obtained from an Et2O solution maintained at -25°C and the structure was determined by single-crystal X-ray diffraction. 1H and 13C NMR spectra of the crystals of [2-Pyr(SiMe3)2C]2SbCl have been obtained in d8-toluene at -30°C, and its decomposition to the stibaalkene was followed by recording spectra as the sample was warmed to 30°C. DFT ab initio calculations have been conducted to investigate the role of pyridyl groups in Me3SiCl elimination as well as the structure and stability of the final stibaalkene. These indicate that the formation of strong Sb-N bonds effectively localizes much of the double-bond character in a C=C rather than Sb=C bond, increasing its overall stability.